1999
DOI: 10.1074/jbc.274.25.18033
|View full text |Cite
|
Sign up to set email alerts
|

The African Swine Fever Virus Prenyltransferase Is an Integral Membrane trans-Geranylgeranyl-diphosphate Synthase

Abstract: In a previous study, it was shown that the protein encoded by the gene B318L of African swine fever virus (ASFV) is a trans-prenyltransferase that catalyzes in vitro the condensation of farnesyl diphosphate and isopentenyl diphosphate to synthesize geranylgeranyl diphosphate and longer chain prenyl diphosphates (Alejo, A., Yá ñ ez, R. J., Rodríguez, J. M., Viñ uela, E., and Salas, M. L. (1997) J. Biol. Chem. 272, 9417-9423). To investigate the in vivo function of the viral enzyme, we have determined, in this w… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
9
0

Year Published

2003
2003
2017
2017

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 18 publications
(9 citation statements)
references
References 35 publications
0
9
0
Order By: Relevance
“…We have shown that p17 has an intrinsic affinity for the ER that it shares with the proteins that localize at this structural domain (59) or that transiently interact with viral membrane precursors (1). A similar behavior has been described for the VV membrane proteins that localize at the membrane of the IV (20), and this is probably related to the necessity of these proteins to integrate early in assembly into ER-derived membranes that have not been completely modified by the viral machinery.…”
Section: Discussionmentioning
confidence: 64%
See 1 more Smart Citation
“…We have shown that p17 has an intrinsic affinity for the ER that it shares with the proteins that localize at this structural domain (59) or that transiently interact with viral membrane precursors (1). A similar behavior has been described for the VV membrane proteins that localize at the membrane of the IV (20), and this is probably related to the necessity of these proteins to integrate early in assembly into ER-derived membranes that have not been completely modified by the viral machinery.…”
Section: Discussionmentioning
confidence: 64%
“…ASFV structural proteins that reside at the inner viral envelope, like p54 (59), or nonstructural proteins that localize at the precursor membranes, like the viral prenyltransferase (1), have an intrinsic affinity for the ER (1,59). To test whether protein p17 can associate with ER membranes when expressed outside the context of ASFV infection, we analyzed its subcellular localization in Vero cells transfected with a plasmid containing the D117L ORF under the control of a T7 RNA polymerase promoter and infected with a recombinant VV that expresses the T7 RNA polymerase.…”
Section: Protein P17 Is Targeted To Er Membranes In Transfected Cellsmentioning
confidence: 99%
“…Inasmuch as 25-hydroxycholesterol lowers transcription of the HMG CoA reductase gene (25), 25-hydroxycholesterol may inhibit HCV replication by depleting cells of geranylgeranyl pyrophosphate, the mevalonate-derived donor of protein geranylgeranylation (7,10). A more general role for host cell geranylgeranylation in viral replication may be inferred from the finding that African swine fever virus, an icosahedral DNA virus, encodes a membrane-bound prenyltransferase that synthesizes geranylgeranyl pyrophosphate (26).…”
Section: Discussionmentioning
confidence: 99%
“…The reduction of virus progeny when geranylation was inhibited after virus entry suggests that intact pools of GGPP or geranylated proteins during a later stage of ASFV infection are also crucial for correct viral replication. In this regard, ASFV encodes a transprenyltransferase (open reading frame B318L) that catalyzes the condensation of farnesyl diphosphate and isopentenyl diphosphate to GGPP and longer chain prenyl diphosphates (1,2). B318L is an essential gene whose expression occurs late during virus infection, and its protein remains associated with precursor viral membranes derived from the endoplasmic reticulum at the viral assembly sites.…”
Section: Discussionmentioning
confidence: 99%